A Short Survey of Automatic Text Summarization Techniques, Algorithms and Their Evaluation - Vipan (International Journal of Intelligent Systems and Applications in Engineering, 2020)
Automatic text summarization has become an indispensable tool in the digital era, empowering users to efficiently extract and distill key information from vast troves of textual data. This comprehensive survey paper delves deep into the diverse techniques and algorithms employed in the field of automatic text summarization. It explores the core methods, including both extractive and abstractive approaches, as well as the underlying algorithms and techniques that power these summarization systems. The paper delves into the capabilities and limitations of these summarization methods, discussing their real-world applications in depth. It also examines the current state-of-the-art in automatic text summarization research, highlighting the notable advancements and innovations that are pushing the boundaries of this dynamic field. The survey provides a thorough and insightful analysis, equipping readers with a nuanced understanding of the key trends, challenges, and future directions in the realm of automatic text summarization. DOI: https://doi.org/10.17762/ijisae.v8i4.7203